(untitled) (Journal of Forestry, 2025)
This is the first study of microelement variability in needles of seven natural populations of Picea omorika (Panč.) Purkyně from Serbia. Seven essential, three usefull, and six toxic microelements were analysed by ICP-Spectrometer. Their range was as follows: Mn > Fe > Zn > Al > Na > B > Cu > Ni > Cr > Cd > Co. The microelements Mo, As, Hg, Pb and Se were detected in traces. Amounts of Al, B, Co, Cr and Na have been recorded in P. omorika needles for the first time. Among usefull microelements the most abundant is Al while among toxic it was Cr. The most southern population, Mileševka canyon, had the highest amounts of Zn, Cu, Ni, Co and Cd and the lowest values of B. Discriminant and Cluster analyses visualized that this population also showed the greatest separation from all other populations. Further research could usefully explore factors that affect the endangerment of P. omorika in its natural habitats or prevent its natural regeneration.